AFFIXAL FORMATION OF DIMINUTIVES IN ENGLISH AND KARAKALPAK LANGUAGES (SCIENCE TIME JOURNAL, 2023)
The article examines formation and classification of diminutive nouns in English and Karakalpak and identify similarities and differences of them in both languages. The term "diminutive forms" refers to the addition of a derivational suffix, mostly to a noun, which results in a new noun form conveying the general meaning of 'little' whether literally or metaphorically. This form can also express intimacy, familiarity, endearment and even lack of respect. Diminutives exist in two languages and they use affixes or affixation to form diminutives. They contribute to the richness of language to get a new or an additional vocabulary.